2008
DOI: 10.1080/14616730802113687
|View full text |Cite
|
Sign up to set email alerts
|

Attachment in adults with high-functioning autism

Abstract: This study assessed attachment security in adults with high-functioning autism spectrum disorders, using the Adult Attachment Interview (AAI; George, Kaplan, & Main, 1996). Of 20 participants, three were classified as securely attached, the same proportion as would be expected in a general clinical sample. Participants' AAIs were less coherent and lower in reflective function than those of controls, who were matched for attachment status and mood disorder. A parallel interview suggested that some aspects of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 56 publications
6
15
0
Order By: Relevance
“…Albeit exploratory, we also showed that, as a group, the individuals with ASD scored higher on avoidant attachment and lower on secure attachment, when compared to a sample of neurotypical individuals. Together, these findings provide indications that-at least to some extent-associations are evident between core autism characteristics and attachment characteristics, a notion that is generally supported by a recent meta-analysis showing an association between the severity of autism characteristics and less secure attachment in children with ASD [22], as well as by other studies showing more insecure attachment toward parents or romantic partners in unmarried [43] or married adults with ASD [44], respectively. However, since research on this topic to date is limited, it currently remains speculative whether the reported feelings of insecure attachment are a result of the social difficulties experienced by individuals with ASD, or conversely, whether difficulties in the social domain are-in part or within a subset of individuals with ASD-a result of a decreased tendency or inability to form secure attachments.…”
Section: Discussionsupporting
confidence: 67%
“…Albeit exploratory, we also showed that, as a group, the individuals with ASD scored higher on avoidant attachment and lower on secure attachment, when compared to a sample of neurotypical individuals. Together, these findings provide indications that-at least to some extent-associations are evident between core autism characteristics and attachment characteristics, a notion that is generally supported by a recent meta-analysis showing an association between the severity of autism characteristics and less secure attachment in children with ASD [22], as well as by other studies showing more insecure attachment toward parents or romantic partners in unmarried [43] or married adults with ASD [44], respectively. However, since research on this topic to date is limited, it currently remains speculative whether the reported feelings of insecure attachment are a result of the social difficulties experienced by individuals with ASD, or conversely, whether difficulties in the social domain are-in part or within a subset of individuals with ASD-a result of a decreased tendency or inability to form secure attachments.…”
Section: Discussionsupporting
confidence: 67%
“…Although Taylor et al (2008) demonstrated the utility of the AAI in a small sample of individuals with high-functioning autistic spectrum disorder and communication difficulties, they excluded participants with IQ's below 70. These researchers likely deemed the AAI as problematic for with adults with IQs below 70.…”
Section: Developmental Assessments Of Adult Attachmentmentioning
confidence: 97%
“…IQ and memory functioning have shown trivial to small associations with classifications of attachment representations (Bakermans-Kranenburg & Van IJzendoorn 1993). However, a recent study on attachment representations and autism excluded participants with an IQ lower than 70 (Taylor et al 2008), and no studies have been performed using the AAI with adults with ID. This may be due to concern that the AAI coding criteria might not discriminate between incoherence due to attachment representations and incoherence due to ID-related deficits in attention, working memory and verbal capacity (Larson et al 2011).…”
Section: Attachment Representationsmentioning
confidence: 99%